AgI cryptates of N,N′-bridged 1,10-diazacyclooctadeca-5,14-diynes: a comparison between the complexes and the free ligands - Gleiter, Rolf; Hirschheydt, Thomas von; Rominger, Frank (European journal of inorganic chemistry, 2000)
The bicyclic diaza alkynes 1−3 react quantitatively with silver triflate to give the corresponding cryptates 4−6. The solid-state structures of the silver(I) complexes 4 and 6 were determined by means of X-ray diffraction studies. A comparison of the molecular structures of 4 and 6 with those of the uncomplexed ligands 1 and 3 reveals drastic changes in the conformations of the ligands. Evidence for an interaction of the silver ions with alkyne units in 4 and 6 was found from a high-field shift of the 13C signal for the sp carbons in the 13C NMR spectrum.
Dedicated to Professor Günter Helmchen on the occasion of his 60th birthday
Im Titel erscheint beim Ausdruck AgI die römische Ziffer I hochgestellt
Gesehen am 23.10.2020
Keywords: Festschrift